1923
DOI: 10.1152/ajplegacy.1923.65.2.234
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic Studies of Muscular Fatigue in Man

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
27
0
5

Year Published

1928
1928
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 0 publications
5
27
0
5
Order By: Relevance
“…The results in the current study are consistent with prior reports showing an increase in the surface EMG amplitude during fatiguing contractions (Cobb and Forbes 1923;Edwards and Lippold 1956;Fuglevand et al 1993;Lind and Petrofsky 1979;Rudroff et al 2008) and the absence of an increase in coactivation of the triceps brachii muscle (cf. Levenez et al 2005;Maluf and Enoka 2005).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results in the current study are consistent with prior reports showing an increase in the surface EMG amplitude during fatiguing contractions (Cobb and Forbes 1923;Edwards and Lippold 1956;Fuglevand et al 1993;Lind and Petrofsky 1979;Rudroff et al 2008) and the absence of an increase in coactivation of the triceps brachii muscle (cf. Levenez et al 2005;Maluf and Enoka 2005).…”
Section: Discussionsupporting
confidence: 93%
“…electromyography; monopolar signals; muscle fatigue; principal component analysis; cluster algorithm; motor control THE EFFECTS OF FATIGUE EMERGE from the beginning of sustained submaximal muscle contractions (Mosso 1906) as indicated by the increase of the amplitude of the surface electromyogram (EMG) needed to sustain the required force (Bigland and Lippold 1954;Cobb and Forbes 1923;De Luca 1984;Edwards and Lippold 1956). Because the motor units recruited from the beginning of a fatiguing contraction exhibit a progressive decrease in discharge rate (Mottram et al 2005;Rudroff et al 2011), the increase in EMG amplitude is generally attributed to the recruitment of additional motor units Gandevia 2001) but can also be influenced by changes in the conduction velocity of motor unit action potentials and the synchronization of motor unit discharge times (Arabadzhiev et al 2010;Yao et al 2000).…”
mentioning
confidence: 99%
“…Since the historic work of Piper (I], the frequencies of the ME signal have been known to decrease during a sustained contrac tion. Cobb and Forbes [2] noted this shift in the frequency components with fatigue, but also observed a consistent in crease in amplitude of the ME signals recorded with surface electrodes. Many other investigators have noted an increase in ME signal amplitude [3]- [11].…”
Section: Introductionsupporting
confidence: 54%
“…The results at the lumbar levels agreed with those of Chapman & Troup (1970) in their study of normal individuals who were loaded in the upright posture. Several other investigators, however, have found an increase in the signal amplitude during sustained muscle contractions of arm and hand muscles (Bigland & Lippold 1954, Cobb & Forbes 1923, Edwards & Lippold 1956). …”
Section: Discussionmentioning
confidence: 95%